2005
DOI: 10.1093/eurheartj/ehi093
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the activity and content of different streptokinase preparations

Abstract: There are wide variations in the activity, purity, and composition of the available streptokinase preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…This was demonstrated in a comparative study by Hermentin et al (2005), in which they compared the activities of 16 different SK preparations and found that only three fulfilled the minimum requirements of the European Pharmacopoeia (Hermentin et al 2005;Thimme, 2005).…”
Section: Purification and Activity Of R-skmentioning
confidence: 95%
“…This was demonstrated in a comparative study by Hermentin et al (2005), in which they compared the activities of 16 different SK preparations and found that only three fulfilled the minimum requirements of the European Pharmacopoeia (Hermentin et al 2005;Thimme, 2005).…”
Section: Purification and Activity Of R-skmentioning
confidence: 95%
“…The information given specifies the acceptable limits for the amount of the API that should be present in a given formulation. However, many examples from a range of drug classes have been published of over/underconcentration of APIs in marketed drugs (see Table ). In some cases, all sampled antibiotics or antimalarials were found to contain API concentrations outside the officially specified limits .…”
Section: Defective Drug Formulationmentioning
confidence: 99%
“…Sixteen preparations of STK available world-wide for clinical use were compared by a SCSA and SDS-PAGE electrophoresis showing wide variations of the activities, purity and composition [10]. Potencies of different preparations of STK were also evaluated by the euglobulin lysis test and the SCSA, showing significant variations between the products available for clinical use [11].…”
Section: Introductionmentioning
confidence: 99%